Reduced primary cilia length and altered Arl13b expression are associated with deregulated chondrocyte Hedgehog signaling in alkaptonuria. Issue 9 (31st March 2017) - Thorpe, Stephen D.; Gambassi, Silvia; Thompson, Clare L.; Chandrakumar, Charmilie; Santucci, Annalisa; Knight, Martin M.
Abstract : Alkaptonuria (AKU) is a rare inherited disease resulting from a deficiency of the enzyme homogentisate 1, 2‐dioxygenase which leads to the accumulation of homogentisic acid (HGA). AKU is characterized by severe cartilage degeneration, similar to that observed in osteoarthritis. Previous studies suggest that AKU is associated with alterations in cytoskeletal organization which could modulate primary cilia structure/function. This study investigated whether AKU is associated with changes in chondrocyte primary cilia and associated Hedgehog signaling which mediates cartilage degradation in osteoarthritis. Human articular chondrocytes were obtained from healthy and AKU donors. Additionally, healthy chondrocytes were treated with HGA to replicate AKU pathology (+HGA). Diseased cells exhibited shorter cilia with length reductions of 36% and 16% in AKU and +HGA chondrocytes respectively, when compared to healthy controls. Both AKU and +HGA chondrocytes demonstrated disruption of the usual cilia length regulation by actin contractility. Furthermore, the proportion of cilia with axoneme breaks and bulbous tips was increased in AKU chondrocytes consistent with defective regulation of ciliary trafficking. Distribution of the Hedgehog‐related protein Arl13b along the ciliary axoneme was altered such that its localization was increased at the distal tip in AKU and +HGA chondrocytes. These changes in cilia structure/trafficking in AKU and +HGA chondrocytes were associated with a complete inability to activate Hedgehog signaling in response to exogenous ligand. Thus, we suggest that altered responsiveness to Hedgehog, as a consequence of cilia dysfunction, may be a contributing factor in the development of arthropathy highlighting the cilium as a novel target in AKU. Abstract : This study investigates whether the rare inherited disease alkaptonuria (AKU) is associated with changes in chondrocyte primary cilia and associated Hedgehog signaling, which is known to mediate cartilage degradation in osteoarthritis. AKU results in alterations to primary cilia structure which are associated with ciliary trafficking defects with the potential to impact a range of fundamental signaling pathways. In particular, AKU chondrocytes demonstrated a complete inability to activate Hedgehog signaling in response to endogenous ligand; which we propose may be the result of the observed dysfunction of cilia structure and trafficking. Thus, we suggest that altered responsiveness to Hedgehog, as a consequence of cilia dysfunction, may be a contributing factor in the development of arthropathy highlighting the cilium as a novel target in AKU.